2004
DOI: 10.1029/2004jd004763
|View full text |Cite
|
Sign up to set email alerts
|

Can large wind farms affect local meteorology?

Abstract: [1] The RAMS model was used to explore the possible impacts of a large wind farm in the Great Plains region on the local meteorology over synoptic timescales under typical summertime conditions. A wind turbine was approximated as a sink of energy and source of turbulence. The wind farm was created by assuming an array of such turbines. Results show that the wind farm significantly slows down the wind at the turbine hub-height level. Additionally, turbulence generated by rotors create eddies that can enhance ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(138 citation statements)
references
References 19 publications
1
124
3
Order By: Relevance
“…In large wind farms, the interaction of the flow and the wind turbines is further complicated by the interaction of the wake of one wind turbine with neighbouring turbines. Besides the changed velocity field around the turbines, there is also evidence that wind turbines affect planetary boundary layer (PBL) processes due to the changed turbulence (Baidya Roy et al, 2004;Calaf et al, 2010;Baidya Roy and Traiteur, 2010;Barrie and KirkDavidoff, 2010;Wang and Prinn, 2010;Lu and Porté-Agel, 2011;Hasager et al, 2013;Fitch et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…In large wind farms, the interaction of the flow and the wind turbines is further complicated by the interaction of the wake of one wind turbine with neighbouring turbines. Besides the changed velocity field around the turbines, there is also evidence that wind turbines affect planetary boundary layer (PBL) processes due to the changed turbulence (Baidya Roy et al, 2004;Calaf et al, 2010;Baidya Roy and Traiteur, 2010;Barrie and KirkDavidoff, 2010;Wang and Prinn, 2010;Lu and Porté-Agel, 2011;Hasager et al, 2013;Fitch et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies show that the large-scale deployment of wind farms alters the local temperature by up to a few degrees [10,13,[15][16][17], reduces precipitation by up to 20% [18], and even mitigates extreme weather [19]. These studies are basically based on limited observation analysis [13,16,20] or model simulations [12,[21][22][23]. However, due to the lack of observations, the effects of wind farms are usually parameterized into numerical models by explicitly increasing either surface roughness length or turbulence kinetic energy [24] and the simulating results from these models do not always agree owing to the model or region adopted [25,26], especially the parameterization model of the wind farm effects.…”
Section: Introductionmentioning
confidence: 99%
“…Wind turbines could modify the surface-atmosphere exchanges by increasing surface roughness [8][9][10], changing the stability of atmospheric boundary layer (ABL) [11], enhancing turbulence in the rotor wakes [12,13], and interrupting the low-level-jet in stable ABL [14]. A few studies show that the large-scale deployment of wind farms alters the local temperature by up to a few degrees [10,13,[15][16][17], reduces precipitation by up to 20% [18], and even mitigates extreme weather [19].…”
Section: Introductionmentioning
confidence: 99%
“…Results have shown that large wind farms do increase scalar fluxes, as it was earlier foreseen by [11]. This increase is the result of two competing effects: one, a major increase of u * ,hi (∼ 50%); two, a decrease due to lower u * ,lo near the ground.…”
Section: Discussionmentioning
confidence: 63%